2014
DOI: 10.4143/crt.2014.46.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Indirectly Promotes M2 Macrophage Differentiation through Stimulation of COX-2/PGE2 Pathway in the Cancer Cells

Abstract: PurposeInterleukin-17 (IL-17) is a proinflammatory cytokine that plays important roles in inflammation, autoimmunity, and cancer. The purpose of this study was to determine if IL-17 indirectly regulates macrophage differentiation through up-regulation of cyclooxygenase-2 (COX-2) expression in the cancer cell lines.Materials and MethodsHuman cervical cancer HeLa, human lung cancer A549, and mouse prostate cancer Myc-CaP/CR cell lines were treated with recombinant IL-17; Western blot analysis, enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 23 publications
(33 reference statements)
1
51
0
Order By: Relevance
“…Our observation that blockade of IL-17A caused a significant reduction in arginase-1 is consistent with a recent study which suggested that IL-17A indirectly mediates arginase-1 production in macrophages via the induction of cyclooxygenase-2 production by HeLa, a human cervical cancer cell line [17]. Moreover, IL-17A has been shown to mediate arginase-1 induction by promoting infiltration of inflammatory monocytes to the site of inflammation [26].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our observation that blockade of IL-17A caused a significant reduction in arginase-1 is consistent with a recent study which suggested that IL-17A indirectly mediates arginase-1 production in macrophages via the induction of cyclooxygenase-2 production by HeLa, a human cervical cancer cell line [17]. Moreover, IL-17A has been shown to mediate arginase-1 induction by promoting infiltration of inflammatory monocytes to the site of inflammation [26].…”
Section: Discussionsupporting
confidence: 80%
“…Since IL-17A has been shown to induce arginase-1 expression by macrophages in recent studies [16,17], we next investigated whether IL-17A played a role in the induction of arginase in our model. Depletion of IL-17A with neutralising antibody, in contrast to depletion of IL-10 and IL-4, significantly reduced the observed level of arginase activity (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proinflammatory cytokine is IL-17, which can stimulate COX-2 expression [73]. MAFs of three SNPs on the promoter of IL-17 receptor achain (À1075 A>G, À947 A>G, À50C>T) were lower in NERD patients than in ATA [74].…”
Section: Immunoglobulin E Receptor Histamine Homeostasis-related Genmentioning
confidence: 99%
“…16 Studies have suggested that IL-17 and COX-2 show a reciprocal effect on each other but have not been previously evaluated in melasma. 17,18 Therefore, we sought to characterize inflammation in this condition by evaluating the cellular infiltrate, the expression of acute and chronic immune inflammatory mediators, and nonimmune inflammation mechanism such as COX-2.…”
Section: Introductionmentioning
confidence: 99%